Polyphenol content and antioxidant capacities of Graptophyllum pictum (L.) extracts using in vitro methods combined with the untargeted metabolomic study - Feda Anisah Makkiyah, Eldiza Puji Rahmi, Fachrur Rizal Mahendra, Faizal Maulana, Rini Anggi Arista, Waras Nurcholis (Journal of Applied Pharmaceutical Science, 2024)
Graptophyllum pictum (L.) Griff contains polyphenols and pharmacological activity for health. In this research, various solvents were employed to examine the total polyphenols, antioxidant capacity, and metabolite profile of G. pictum leaf extract. The chemometric analysis evaluated secondary metabolites from liquid chromatography with tandem mass spectrometry from G. pictum with various solvents on total polyphenol and antioxidant capacity. Analysis of total polyphenols revealed that the highest total phenolic content was 32.17 mg gallic acid equivalent g−1 DW in ethanol solvent, while the highest total flavonoid content was 9.14 quercetin equivalent g−1 DW in ethyl acetate solvent. Meanwhile, the highest radical scavenging capacity of 2,2-diphenyl-1-picrylhydrazyl was 29.71 μmol TE g−1 DW in ethanol solvent, and the highest radical scavenging capacity of 2,2’-azino-bis (3-ethylbenzthiazoline-6-sulfonic acid) was highest at 33.27 μmol TE g−1 DW in ethanol solvent. Furthermore, the reduction capacity value used a ferric-reducing agent. The highest ferric-reducing antioxidant power was 52.54 TE g−1 DW in ethanol solvent, and the highest reduction of cupric-reducing antioxidant capacity was 65.94 μmol TE g−1 DW in ethanol solvent. The results of chemometric analysis using hierarchical cluster and principal component analysis showed that secondary metabolites such as phenolic and flavonoid groups in ethanol extract had the best potential for various antioxidant activities.
Keywords: Graptophyllum pictum, polyphenol, antioxidant, metabolomic, chemometrics